Application of Pulsed Field Gel Electrophoresis for Study of Genetic Diversity in Mycobacterium tuberculosis Strains Isolated From Tuberculosis Patients - Khosravi, Azar Dokht (Kowsar, 2014)
BACKGROUND: Mycobacterium tuberculosis genotyping can effectively improve tuberculosis (TB) control programs by controlling disease transmission. Pulsed field gel electrophoresis (PFGE) is a particularly powerful tool for determination of clonal identity of bacteria providing information for understanding and controlling the spread of disease. OBJECTIVES: The aim of present study was to investigate the genetic diversity of M. tuberculosis strains in Khuzestan province by the PFGE technique. PATIENTS AND METHODS: In total, 80 M. tuberculosis positive cultures were obtained from tuberculosis patients. PFGE was performed on 60 PCR-confirmed isolates by using DraI and XbaI restriction enzymes according to standard protocols. Plugs containing digested DNA were then loaded on agarose gels and run using contour-clamped homogenous electric fields. RESULTS: Fifty distinct DNA banding patterns were obtained by digestion of DNA with DraI and 38 DNA banding patterns by digestion with XbaI restriction enzymes. The patterns comprised of 17 different clusters in which cluster I was the major one, containing six strains. Three clusters contained three strains each and the 13 remaining clusters comprised of two strains each. Digestion with DraI yielded 15-20 DNA fragments with 50-485 kb size, while digestion by XbaI produced DNA fragments with a size smaller than 50-242 kb. CONCLUSIONS: Despite the ability of PFGE for study of genetic diversity of many mycobacterial species and it being considered as a robust and useful tool, in this study we only found a 15% epidemiological relationship amongst the isolates. Thus, for higher discrimination of genotypic clusters among M. tuberculosis clinical isolates, the application of more sophisticated complementary techniques is required.